تعليم اللغة العربية لأغراض خاصة في ماليزيا:دراسات وتطبيقات = Ta’lim al-lughah al-arabiyyah li aghradh khassah fi maliziya: dirasat wa tatbiqat - Chik, Abdul Rahman (Kolej Universiti Insaniah, 2010)
A survey on studies conducted in the area of Arabic for Specific Purposes (ASP). There are theses, papers and articles written by researchers.